Type 2 autoimmune hepatitis: Genetic susceptibility - Lapierre, Pascal; Alvarez, Fernando (Frontiers in Immunology, 2022)
Two types of autoimmune hepatitis (AIH) are recognized; AIH-1 is characterized by the presence of anti-nuclear and/or anti-smooth muscle autoantibodies, while AIH-2 is associated with the presence of anti-Liver kidney microsome and /or anti-Liver Cytosol antibodies. The autoantigens targeted by AIH-2 autoantibodies are the cytochrome P450 2D6 and Formiminotransferase-cyclodeaminase for anti-LKM1 and anti-LC1 respectively. Both autoantigens are expressed in hepatocytes at higher levels than in any other cell type. Therefore, compared to AIH-1, the autoantigens targeted in AIH-2 are predominantly tissue-specific. Distinct clinical features are specific to AIH-2 compared to AIH-1, including diagnosis in younger patients (mean age 6.6 years), onset as fulminant hepatitis in very young patients (3 years of age or less), higher frequency in children than in adults and is frequently associated with extrahepatic T cell-mediated autoimmune diseases. AIH-2 is also often diagnosed in patients with primary immunodeficiency. AIH-2 is associated with specific HLA class II susceptibility alleles; DQB1*0201 is considered the main determinant of susceptibility while DRB1*07/DRB1*03 is associated with the type of autoantibody present. HLA DQB1*0201 is in strong linkage disequilibrium with both HLA DRB1*03 and DRB1*07. Interestingly, as in humans, MHC and non-MHC genes strongly influence the development of the disease in an animal model of AIH-2. Altogether, these findings suggest that AIH-2 incidence is likely dependent on specific genetic susceptibility factors combined with distinct environmental triggers.